Konsumsi Menuju Konstruksi Masyarakat Konsumtif - M. Chairul Basrun Umanailo; Mansyur Nawawi; Sukainap Pulhehe (SIMULACRA: JURNAL SOSIOLOGI, 2018)
This article aims to analyze public consumption actions as a practice model that will create a new model in understanding consumption patterns to become consumptive. The pattern of public consumption in its development has shifted due to the availability of modern technology and facilities. The approach used in this paper is library research, with data analysis techniques in the form of content analysis with the aim of obtaining valid inferences and can be re-examined based on the context. the presence of technology as a representation of facilities in meeting needs is able to encourage the creation of social change, such as the spread of consumerism culture, changes in dress and lifestyle modes where these conditions are institutionalized in the cultural structure of society so that consumption of goods is not based solely on the logic of needs, but will include substantial someone's emotions. The situation systematically shifts traditional values and leads to global behavior. Consumption towards the construction of consumptive society is a conceptual and historical illustration for all of us to further understand the shifting consumption into consumptive practices.